Pengembangan PENGEMBANGAN KEMAMPUAN MAHASISWA PGSD DALAM MEMBUAT MEDIA PEMBELAJARAN MELALUI METODE PEMBELAJARAN RESITASI BERBANTUAN YOU TUBE - Ratih Purnamasari (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2019)
This study aims to find out how the situation of the learning process by using the tube-assisted recitation method and knowing the ability of students to create learning media through you tube assisted recitation learning methods can develop. This research is a descriptive qualitative study. The subjects of this study were 5th semester students, PGSD FKIP Pakuan University. The instruments used were observation, interviews and documentation. The results showed that you tube assisted recitation method can improve student independence, motivation to display the best, creativity and self-confidence of students in making learning media in elementary school. But there needs to be an emphasis on the importance of involving IT and the importance of including a reference list.